Assessment of thiamine and riboflavin levels in common green leafy vegetables grown in Shariatpur, Bangladesh - Aminul Islam; Md Zakir Sultan; Md Ashraf Ali; Md Lemon Mia; Md Abdus Salam (Heliyon)
Thiamine (vitamin B1) and riboflavin (vitamin B2) are essential vitamins because of their important health impact. Twelve different green leafy vegetable-samples including Solanum nigrum, Alternanthera sessilis, Amaranthus spinosus, Cucurbita moschata, Pisum sativum, Chenopodium album, Alternanthera philoxeroides, Amaranthus blitoides, Glinus oppositifolius, Amaranthus viridis, Coccinia grandis, and Corchorus capsularis indigenous to Shariatpur district in Bangladesh were collected, dried, stored and analyzed. The extraction procedures involved acid hydrolysis followed by enzymatic hydrolysis of the dried vegetable samples. A Shimadzu Prominence HPLC system operating in isocratic elution mode on a C18 column (4.6 mm × 250 mm, 5 μm) was utilized to achieve chromatographic separation of the vitamins while a fluorescence detector recorded the signals. The outcome showed that the HPLC method offered excellent sensitivity and selectivity for thiamine and riboflavin determination in leafy vegetables. The calibration curves exhibited good linearity (R2 > 0.99), and the recovery percentages were found to be excellent also, at 108.22 % and 100.22 % for thiamine and riboflavin, respectively. Comparative analyses revealed variations in thiamine and riboflavin contents in different leafy vegetables, highlighting the importance of including a diverse range of leafy vegetables in the diet to meet recommended daily intake levels of these vitamins.